Technology, Drivers, and Fraud Prevention in The Public Sector: a Scoping Review - Maharani, Maharani; Utomo, Dwi Cahyo (Universitas Muhammadiyah Semarang, 2026)
Financial fraud in the public sector remains a persistent challenge that undermines governance, accountability, and public trust. Although previous reviews have examined aspects of fraud and forensic accounting, limited attention has been given to how technology, fraud drivers, and prevention mechanisms interact within the public sector context. This study aims to map and synthesize recent literature to understand the role of technology, key drivers, and prevention strategies in mitigating public sector financial fraud. Using Arksey and O’Malley (2005) scoping review framework, this study systematically identified and analyzed 10 peer-reviewed journal articles published between 2021 and 2025. The findings reveal that technologies such as big data analytics and blockchain significantly enhance fraud detection and transparency, while weak internal controls and permissive organizational culture remain major drivers of fraud. Preventive mechanisms, including forensic auditing and strong governance structures, demonstrate effectiveness in reducing fraud risk. This review contributes to the literature by integrating three dimensions, technology, fraud drivers, and prevention, in a single analytical framework, offering a more comprehensive understanding of public sector fraud mitigation than prior reviews. The study highlights research gaps in long-term policy evaluation and cross-sectoral learning between public and private entities, providing directions for future research and policy development.